The value of sales forecasting for firms with high strategic adaptation ability : a case study in the automotive industry / Faizal Mohamed Yusof - Mohamed Yusof, Faizal (Institute of Graduate Studies, UiTM, 2012)
The purpose of this study is to delineate and signify the value of sales forecasting by examining the relationship between strategic adaptation ability and sales forecasting management. In doing so, this study also addressec an on-going debate on whether there should be ‘less or more’ forecasting in a competitive and volatile market environment. In addressing this gap, UMW Toyota (UMWT), an automotive firm with high strategic adaptation ability was identified for the study. This study employs a mixed-methods case study approach which is predominantly qualitative. A quantitative strategic adaptation framework based on Eunni et al. (2005) provides the context for resulting organizational adaptation capability of UMWT. Data were collected from Malaysian Automotive Association (MAA) and companies commission of Malaysia (CCM). The sales Forecasting Benchmarking Model (SFBM) from mentzer and Moon (2005) offers a framework to qualitatively analyse the sales forecasting management of UMWT.